Physical activity, fatigue and quality of life during a clinical adjuvant treatment of breast cancer: a comparative study - Boing,Leonessa (2018)
The objective of the study was to compare the physical activity, fatigue and quality of life of patients during breast cancer treatment and to investigate the association between these variables. It was included 122 women in clinical treatment at the Cancer Research Center (CEPON) in Florianópolis, SC. We used a questionnaire with general information, physical activity (IPAQ - short), fatigue (Piper fatigue) and quality of life (EORTC QLQ - C30). One-way ANOVA with Scheffe's post-hoc, Chi-square, and univariate and multiple linear regression (p <0.05) were used. It was observed a greater walking time and total physical activity for the patients in the hormone therapy. In the fatigue, worse scores were presented by the patients in the chemotherapy. In the quality of life, there was a difference in the symptomatic scale, with worse scores on the subscales of nausea and vomiting, pain and loss of appetite for patients on chemotherapy and constipation for radiotherapy. It was identified an association between the increase of the physical activity with the improvement of the physical, social function and symptoms of the fatigue, regardless of the type of treatment or age. Patients in the hormone therapy practiced more physical activity, and those in chemotherapy had worse side effects. It is necessary to encourage physical activity during treatment, since benefits in quality of life and fatigue are evidenced.